Changes in neuronal activity across the mouse ventromedial nucleus of the hypothalamus in response to low glucose: Evaluation using an extracellular multi‐electrode array approach. (23rd February 2020) - Hanna, Lydia; Kawalek, Tristan J.; Beall, Craig; Ellacott, Kate L. J.
Abstract: The hypothalamic ventromedial nucleus (VMN) is involved in maintaining systemic glucose homeostasis. Neurophysiological studies in rodent brain slices have identified populations of VMN glucose‐sensing neurones: glucose‐excited (GE) neurones, cells which increased their firing rate in response to increases in glucose concentration, and glucose‐inhibited (GI) neurones, which show a reduced firing frequency in response to increasing glucose concentrations. To date, most slice electrophysiological studies characterising VMN glucose‐sensing neurones in rodents have utilised the patch clamp technique. Multi‐electrode arrays (MEAs) are a state‐of‐the‐art electrophysiological tool enabling the electrical activity of many cells to be recorded across multiple electrode sites (channels) simultaneously. We used a perforated MEA (pMEA) system to evaluate electrical activity changes across the dorsal‐ventral extent of the mouse VMN region in response to alterations in glucose concentration. Because intrinsic (ie, direct postsynaptic sensing) and extrinsic (ie, presynaptically modulated) glucosensation were not discriminated, we use the terminology 'GE/presynaptically excited by an increase (PER)' and 'GI/presynaptically excited by a decrease (PED)' in the present study to describe responsiveness to changes in extracellular glucose across the mouse VMN. We observed that 15%‐60% of channels were GE/PER, whereas 2%‐7% were GI/PED channels. Within the dorsomedial portion of the VMN (DM‐VMN), significantly more channels were GE/PER compared to the ventrolateral portion of the VMN (VL‐VMN). However, GE/PER channels within the VL‐VMN showed a significantly higher basal firing rate in 2.5 mmol l ‐1 glucose than DM‐VMN GE/PER channels. No significant difference in the distribution of GI/PED channels was observed between the VMN subregions. The results of the present study demonstrate the utility of the pMEA approach for evaluating glucose responsivity across the mouse VMN. pMEA studies could be used to refine our understanding of other neuroendocrine systems by examining population level changes in electrical activity across brain nuclei, thus providing key functional neuroanatomical information to complement and inform the design of single‐cell neurophysiological studies.